Pass key to the SAT - Green, Sharon, 1939-; Green, Sharon, 1939-; Wolf, Ira K. (Hauppauge, N.Y. : Barron's Educational Series, 2010)
A preparation manual for the SAT that includes two full-length practice exams, answer explanations, tips for completing the essay portion of the exam, and strategies for improving test scores.
"Adapted from Barron's SAT, c2010"--T.p. verso.
Young Adult.
Young Adult
Keywords: SAT (Educational test) -- Study guides; Universities and colleges -- United States -- Entrance examinations -- Study guides; Colleges and universities -- United States -- Entrance examinations -- Study guides; Scholastic Assessment Test -- Study guides